Medicinal plants of the mountain West - Moore, Michael, 1941-2009 (Museum of New Mexico Press, 2003)
"Herbalist Michael Moore, one of the founders of the modern herbal medicine movement in the United States, here updates in expanded form his classic work Medicinal Plants of the Mountain West, the indispensable field guide to identifying southwestern medicinal plants and their preparation and use. Drawing on a thirty-five-year career as a teacher, merchant, and alternative-medicine practitioner, Moore has produced the most accessible herbal available for professionals and non-professionals alike. Practical and user-friendly, this guide to one hundred twenty-nine medicinal plants, with its extensive therapeutic index covering hundreds of common ailments and conditions, provides essential herbal remedies for the panoply of nonacute diseases left unaddressed by standard-practice medicine."--BOOK JACKET.